Features of public-private partnership financing as an economic and legal tool for sustainable development - Петруненко, Ярослав Вікторович; Петруненко, Я. В.; Петруненко, Ярослав Викторович; Petrunenko, Yaroslav V.; Petrunenko, Iaroslav V.; Васильєва, Наталія Вікторівна; Васильєва, Н. В.; Васильева, Наталия Викторовна; Vasylieva, Nataliia V.; Приліпко, Сергій Михайлович; Приліпко, С. М.; Прилипко, Сергей Михайлович; et al. (WSEAS, 2021)
The economic transition from a market to a social model requires a review of the role of the state and representatives of business structures in the economic system. Various forms of their interaction are becoming increasingly important, the main of which are public-private partnerships aimed at financing, formation, and implementing socially important projects. The purpose of the study is to analyze and evaluate the parameters of interaction between the state and the private sector in terms of improving the socio-economic partnership based on the provisions of the concept of public-private partnership (PPP). To achieve the goal were used such methods: analysis and synthesis; formalization and grouping; systematization and logical abstraction. The practice of the Public-Private Partnership Center of the Republic of the Philippines shows that the rational use of social partnership financial instruments will allow the state to reduce the budget burden, ensure infrastructure development, increase employment, develop private enterprises and improve the quality of goods and services. It is noted that the level of public-private partnership use in the world differs significantly, and therefore requires further intensification of efforts to stimulate its use, including due to the wide range of significant benefits of its use for the economy and the population in particular. Public-private partnerships are becoming increasingly popular as they provide many important benefits. In particular, the opportunity to obtain additional financial resources, including through additional investments, quality projects involving professional companies, open access to innovative technologies, and priority opportunities for the state to direct funds to specific areas. Thus, the direction of further research may be to determine the details of the functioning of projects in the framework of public-private partnerships. It is also important to conduct a pre-investment analysis, check the effectiveness of financing, prepare appropriate recommendations for each project stage.

Перехід економіки від ринкової до соціальної моделі потребує перегляду ролі держави та представників бізнес-структур в економічній системі. Все більшого значення набувають різноманітні форми їх взаємодії, основними з яких є державно-приватне партнерство, спрямоване на фінансування, формування та реалізацію соціально значущих проектів. Метою дослідження є аналіз та оцінка параметрів взаємодії держави та приватного сектора з точки зору вдосконалення соціально-економічного партнерства на основі положень концепції державно-приватного партнерства (ДПП). Для досягнення мети були використані такі методи: аналіз і синтез; формалізація та групування; систематизація та логічне абстрагування. Практика Центру державно-приватного партнерства Республіки Філіппіни показує, що раціональне використання фінансових інструментів соціального партнерства дозволить державі зменшити бюджетне навантаження, забезпечити розвиток інфраструктури, збільшити зайнятість, розвивати приватні підприємства та підвищити якість товарів та послуг. Зазначається, що рівень використання державно-приватного партнерства у світі суттєво відрізняється, а тому потребує подальшої активізації зусиль щодо стимулювання його використання, у тому числі через широкий спектр суттєвих переваг його використання для економіки та населення зокрема. Державно-приватне партнерство стає все більш популярним, оскільки воно дає багато важливих переваг. Зокрема, можливість отримати додаткові фінансові ресурси, у тому числі за рахунок додаткових інвестицій, якісних проектів за участю професійних компаній, відкритого доступу до інноваційних технологій, пріоритетних можливостей держави спрямувати кошти на конкретні напрямки. Таким чином, напрямом подальших досліджень може бути визначення деталей функціонування проектів у рамках державно-приватного партнерства. Також важливо провести передінвестиційний аналіз, перевірити ефективність фінансування, підготувати відповідні рекомендації для кожного етапу проекту.
Petrunenko I. Features of public-private partnership financing as an economic and legal tool for sustainable development / I. Petrunenko, N. Vasylieva, S. Prylipko, N. Kryzyna, S. Lavrynenko, I. Zhuk // Transactions on Environment and Development. - Vol. 17. - WSEAS, 2021. - Р. 533-541.
Keywords: Public-Private Partnership; PPP Contract; PPP Financing; PPP Advantages & Disadvantages; Republic of the Philippines` Public-Private Partnership Center; Державно-приватне партнерство; договір ДПП; фінансування ДПП; переваги та недоліки ДПП; Центр державно-приватного партнерства Республіки Філіппіни; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics; Research Subject Categories::LAW/JURISPRUDENCE